Swallow contrast-enhanced ultrasonography detects a tiny cervical esophageal diverticulum missed on barium esophagography: a case report - Feng Yu; Yaoyao Li; Shengting Chen; Chengxiang Zhou (Frontiers in Medicine, 2026)
Background Barium esophagography is standard for esophageal lesions but may miss subtle small diverticula. Prior literatures have reported swallow contrast-enhanced ultrasonography (SCEUS) for esophageal diverticulum detection. This case presents a tiny cervical esophageal diverticulum misclassified as C-TIRADS 4A thyroid nodule, undetected by barium esophagography but visualized by SCEUS. We describe the imaging characteristics and incremental value of microbubble contrast for this easily misdiagnosed entity. Case presentation We report the case of a 38-year-old Chinese man with no initial clinical symptoms related to the esophagus. In June 2019, a routine ultrasonographic examination revealed a solid nodule easuring approximately 5. 1 × 3.5 mm in the posteromedial aspect of the middle and upper pole of the left thyroid lobe. This nodule demonstrated close anatomical proximity to theadjacent esophageal wall, raising suspicion for an esophageal origin. Subsequent barium esophagography was performed, which demonstrated no significant abnormalities. Given the absence of related clinical symptoms, the patient was placed on an annual follow-up protocol. On January 18, 2025, conventional gray-scale ultrasonography revealed a 1-mm increase in the maximum diameter of the lesion compared with the initial examination, prompting further evaluation with SCEUS, which clearly confirmed the presence of an esophageal diverticulum in the upper-middle third of the left thyroid lobe measuring 5.6 × 3.8 mm in size. For intuitive visual comparison, one healthy volunteer was enrolled to acquire standard SCEUS images depicting normal physiological swallowing morphology. Conclusion In this single case, SCEUS visualized a tiny cervical esophageal diverticulum undetected by barium esophagography, helping avoid unnecessary thyroid resection. Microbubble contrast provides dynamic real-time delineation of diverticular communication that cannot be fully resolved by plain water swallow ultrasound. However, this single observation cannot support generalized superior diagnostic performance of SCEUS. Further cohort studies are needed to validate the clinical utility of SCEUS for small esophageal diverticula mimicking thyroid nodules.